1983
DOI: 10.1111/j.1476-5381.1983.tb10495.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of histamine receptors in the release of renin

Abstract: 1 The effect of intrarenal histamine, dimaprit (H2-agonist) and 2-(2-pyridyl) ethylamine (Hl-agonist) on renin release was examined in anaesthetized dogs.2 In dogs with intact kidneys, histamine and dimaprit administration resulted in renal vasodilatation, a two fold increase in urinary sodium excretion, and no change in renal renin release. 2(2-Pyridyl) ethylamine administration resulted in renal vasodilatation, a 25% decrease in urinary sodium excretion and a significant increase in renin release. 3 In dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…These findings arc in agreement with those of sev eral investigators [1,3,9,10]. H , receptors also appeared to mediate the effect of hista mine on FEN (1.…”
Section: H R Receptor Mediation O F Histamine Effectssupporting
confidence: 82%
See 4 more Smart Citations
“…These findings arc in agreement with those of sev eral investigators [1,3,9,10]. H , receptors also appeared to mediate the effect of hista mine on FEN (1.…”
Section: H R Receptor Mediation O F Histamine Effectssupporting
confidence: 82%
“…However, if the FENa were dependent on hemodynamic changes, then tripelennamine alone should also have reduced FENa. Gerber and Nies [3] recently reported that PEA significantly in creased RBF but decreased urinary sodium excretion. They suggested that the slight but nonsignificant decline in G F R may have been partly responsible for the decrease in urinary sodium excretion.…”
Section: //-Receptor Mediation O F Histamine Effectsmentioning
confidence: 99%
See 3 more Smart Citations